The Importance of Intercultural Communicative Competence to IAIN Parepare Students - Abdul Haris Sunubi; Hilmiyah Akib (ELITE JOURNAL, 2023)
The aim of this research is to know the interculture communicative competence for millenial students because in class interaction, there are alot of students derive from different place,tribe and local language. The students can share information, experience, knowledge each other to build togetherness in daily activities in the class and in the social interaction. Keywords: intercultural, communicative competence, millennial student